GAMBARAN KARAKTERISTIK DAN STATUS IMUNISASI PENDERITA DIFTERI DI PROVINSI JAWA TIMUR TAHUN 2018 - Wigrhadita, Dwi Rismayanti (Fakultas Kesehatan Masyarakat, Universitas Jember, 2019)
In 2016 East Java was the region with the highest cases of diphtheria, namely 209 cases with 6 deaths. In 2017 diphtheria cases in East Java increased to 460 cases with 16 deaths, and continued to increase in 2018, namely 758 cases with a death rate of 3 people. This research aims to describe the characteristics and immunization status of diphtheria sufferers in East Java Province in 2018. This research is a descriptive research type with a cross sectional study design. The research population were all people who were declared diphtheria in East Java Province in 2018. The method of sampling is to use the total population. The variables were the characteristics and immunization status of diphtheria sufferers. Data were analyzed using univariate analysis with frequency table. The result shows that characteristics of diphteria sufferers were dominated by age ≥19 years (33.11%) and male sex (50.6%). Diphtheria sufferers are dominated by incomplete immunization status (98.15%). The conclusion shows that completeness of 7-dose diphtheria immunization plays an important role in the occurrence of diphtheria cases in East Java Province in 2018, especially patients who have not carried out immunizations at all.